2013
DOI: 10.1016/j.eurpolymj.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Renewable sulfur-containing thermoplastics via AB-type thiol-ene polyaddition

Abstract: Polythioethers with molar masses up to 40 kDa were prepared by UV-or thermal initiated thiolene polyaddition polymerization of an aliphatic α-olefinic ω-thiol, an AB-type monomer derived from 10-undecenoic acid, which is a bio-sourced building block obtained from castor oil. The low polarity of the starting compound and the stability of the thioether functions formed during polymerization allowed for the synthesis of polymers with similar structures to existing bulk and engineering plastics such as polyethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 21 publications
(15 reference statements)
1
26
0
Order By: Relevance
“…Interestingly, the melting point for silylated P2f barely increased from 64.0 to 65.8 °C. In general, DSC analysis of P2a – P2e showed two close melting peaks, which is common for oxidized thiol‐ene polymers and known from literature . Such behavior is indicative of the recrystallization of different crystal forms in polar polymeric materials and also observed, for instance, for Nylon 6.6 .…”
Section: Synthesis Of Dithiolssupporting
confidence: 67%
“…Interestingly, the melting point for silylated P2f barely increased from 64.0 to 65.8 °C. In general, DSC analysis of P2a – P2e showed two close melting peaks, which is common for oxidized thiol‐ene polymers and known from literature . Such behavior is indicative of the recrystallization of different crystal forms in polar polymeric materials and also observed, for instance, for Nylon 6.6 .…”
Section: Synthesis Of Dithiolssupporting
confidence: 67%
“…Sulfones exhibit a high polarity and thus, changes in thermal behaviour and crystallinity of the related polymers are expected [30]. It was found that hydrogen peroxide is able to selectively oxidize the thioether to sulfoxide or to sulfone groups depending on the reaction temperature [31].…”
Section: Synthesis Of Pso(la-b-teha-b-la) Triblock Copolyesters Sulfonesmentioning
confidence: 99%
“…Du Prez and co-workers [195] used thioacetates in the preparation of bio-sourced polythioethers. Starting from 10-undecenoic acid as a renewable resource, it was possible to prepare an α-olefinic ω-thiol monomer.…”
Section: Thioestersmentioning
confidence: 99%